Factors associated with utilization of quality antenatal care: a secondary data analysis of Rwandan Demographic Health Survey 2020 - Sserwanja, Quraish; Nuwabaine, Lilian; Gatasi, Ghislaine; Wandabwa, Julius N.; Musaba, Milton W. (BMC health services research, 2022)
Over the last decade, progress in reducing maternal mortality in Rwanda has been slow, from 210 deaths per 100,000 live births in 2015 to 203 deaths per 100,000 live births in 2020. Access to quality antenatal care (ANC) can substantially reduce maternal and newborn mortality. Several studies have investigated factors that influence the use of ANC, but information on its quality is limited. Therefore, this study aimed to identify the determinants of quality antenatal care among pregnant women in Rwanda using a nationally representative sample.